Graditi partizanski spomin v socialistični Jugoslaviji - Klabjan, Borut (Acta Histriae, 2022)
The article analyses local practices of memory activism among Slovenes in the first decade after the Second World War. While in recent years Much of the scholarly work and popular production focuses on the officially sanctioned memory landscape taking for granted that monuments are installed by the Yugoslav government in a unilateral top-down direction, a more in-depth research shows how vernacular memory cultures produced several examples of bottom-up memory signs. Thus, Slovenia had in 1961 the highest number of partisan memorials in Yugoslavia: 4035. However, it would be misleading to think that this memory activism developed without disagreements. Even if, since 1948, when it was founded the Federation of Associations of Combatants, this umbrella organization was in charge for the control and the coordination of the construction of monuments to the fallen, local committees continued to have a primary role. The construction of memorials involved the cooperation of many individuals (architects, engineers, as well as intellectuals who wrote tombstone inscriptions) and companies (particularly construction companies) in an intermingling of private initiatives and public support, memory activism and socialist narratives, official remembrance and private mourning. Often local committees however, in contrast with the veteran’s association and State institutions, imposed their view on the form and the content of the memorial site. These tensions invert the perspective of a civil society as a passive subject of decision making, dependent on and subjugated to the socialist regime and shows that local communities seek to define themselves and their memory in ways that might be at variance with desires of central offices.
Keywords: memorials; memory; monuments; Narodnoosvobodilni boj (1941-1945); partisans; Partizani; Slovenia; Spomeniki; spomeniki NOB; Svetovna vojna (1939-1945); World War II; Yugoslavia